Knowledge of occupational health hazards and practice of personal protective equipment among fabrication workers in Kathmandu district, Nepal - Bibeka Shrestha, Dr; Naresh Manandhar, Dr; Sunil Kumar Joshi, Prof (Occupational Health and Safety Society of Nepal, 2020)
Background: Fabrication work is one of the hazardous occupations in which workers are exposed to different occupational hazards and injuries. But the workers lack proper knowledge about protecting themselves from those hazards. This study was conducted, to assess knowledge about occupational health hazards among fabrication workers and to find out the practice of Personal Protective Equipment (PPE) in fabrication works. Methods: A cross-sectional study was conducted among 394 fabricator workers of Kathmandu District by using a multi-stage sampling technique. Participants were interviewed with a pre-tested semi-structured questionnaire. Results: All the participants were male, and their age ranged from 19-60 years with the mean age of 32.3 years. 71.3% of participants had work-related health complains, among which arc eye (85.76%) was the most common. Among them, 87.1% had at least used one PPE. There was a significant association between awareness about occupational hazards and work experience of fabrication workers (p=0.001), and the practice of PPE with religion (p<0.01). Conclusions: This study found that fabrication workers were aware of occupational hazards and the use of PPE during the fabrication work. But the practice of PPE was not enough to protect them from the occupational hazards.